(untitled) (Orthodontic Journal of Nepal, 2022)
Introduction: The Aim of this study is to compare the concentration of salivary leptin levels between underweight and overweight individuals and its significance in orthodontic tooth movement. Methods: Fourty five underweight and overweight female subjects. Materials and Method: Fourty five underweight and overweight female subjects were taken in this study and they are divided into two groups, group I (underweight) and group II (overweight) depending on their mean body mass index. Angles class I malocclusion with bimaxillary protrusion were taken into this study. All subjects underwent upper first premolar extraction, and distal force is applied with lacebacks to maxillary canine. Salivary leptin samples were collected before force application (To), one hour after appliance placement T2, and one month after appliance placement (T3). Result: Overweight individuals show increased salivary leptin concentration three times greater than underweight individuals. Orthodontic tooth movement is decreased in overweight individuals when compared with underweight individuals. Conclusion: Increased salivary leptin levels showed a decreased tooth movement in overweight individuals than underweight individuals who showed decreased salivary leptin levels. Obese individuals require more orthodontic treatment duration time when compared with lean individuals.